UNIT 18.9 Finding Pathogenic Nucleic Acid Sequences in Next Generation Sequencing Data. (1st July 2015) - Parfenov, Michael; Seidman, J.G.
Abstract : Viruses and bacteria are established as one of the main causes of human diseases from hepatitis to cancer. Recently, the presence of such pathogens has been extensively studied using human whole genome and transcriptome sequencing data. However, detecting and studying pathogens via next generation sequencing data is a challenging task in terms of time and computational resources. In this protocol we give instructions for a simple and quick method to find pathogenic DNA or RNA and detect possible integration of the pathogen genome into the host genome. © 2015 by John Wiley & Sons, Inc.